Kepuasan Pasien Pengguna Badan Penyelenggara Jaminan Sosial Berbasis Kualitas Pelayanan - Hardiana, Hardiana; Gemina, Dwi; Gunawan, Rachmat; Yuningsih, Erni; Yulianingsih, Yulianingsih (Innovative: Journal Of Social Science Research, 2024)
This research aims to determine and analyze the quality of service, both simultaneously and partially, on the satisfaction of patients using the Social Security Administering Agency at the Ciawi Bogor Community Health Center. The sample size was 100 respondents taken using simple random sampling technique with accidental sampling method with criteria; 1) patients who have sought treatment at the Ciawi Community Health Center at least once; 2) patients who are mature enough to fill out the questionnaire are 17 years old. The questionnaire was tested using validation, reliability and classical assumption tests. The results of this test are valid, reliable, and can be used for regression data. The analytical method used in this research is a descriptive and verification method with a quantitative approach. The research results show that service quality variables, both simultaneously and partially, have a positive and significant effect on patient satisfaction at the Ciawi Bogor Community Health Center. The driver of patient satisfaction using the Social Security Administering Agency at the Ciawi Bogor Community Health Center is reliability.